WORLD-VIEW AND SALVATION ACCORDING TO SAlVA SIDDHANTA - lrudayaraj, Xavier (Journal of Dharma, 1979)
In the present-day world ’Freedom’ and ’Liberation’ seem to be the catch-words both in World-view and Salvation. Indeed, freedom is the perennial and ceaseless quest of man. There has ever been and ever will be this constant struggle to become more free. One often hears about freedom from economic, social and cultural bond ages. But is not life itself subject to bondage?